Job Satisfaction Sebagai Mediasi dalam Peningkatan Turnover Intention Mitra Driver Gojek Area Kota Mataram Pasca Pandemi Covid-19 - Isra Dewi Kuntary Ibrahim; Irwan Cahyadi; Raden Bagus Faizal Irany Sidharta; Agus Hermanto (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2021)
This study aims to identify the significant influence between Work Motivation and Job Insecurity on Job Satisfaction and Turnover Intentions of Gojek Driver Partners in the Mataram City Area pasca the Covid-19 Pandemic. Collecting data using the method of determining the sample, namely the census with a total of 102 people collected questionnaires from 150 total of respomdent. Analysis and hypothesis testing using Partial Least Square (PLS) with research instruments using a questionnaire via an online google form. The results showed that there was a negative and insignificant effect of work motivation on turnover intentions, a positive and significant effect of work motivation on job satisfaction, a negative and significant effect of job insecurity on turnover intentions, a negative and significant effect of job insecurity on job satisfaction, a positive and significant effect job satisfaction on turnover intentions. full mediating and significant effect of work motivation on turnover intentions through job satisfaction and partial mediating and significant effect of job insecurity on turnover intentions through job satisfaction.